More Reliable Approach than Blood Glucose Value is Needed in Assessment of Cell Metabolism - Simon, Kornel; Wittmann, Istvan (Current Overview on Disease and Health Research Vol. 2, 2022)
We studied the relationship between blood glucose values and metabolic states in various pathological conditions. In clinical guidelines, near-normoglycaemia is recommended as the basic therapeutic target in diabetes mellitus. This proposal suggests that euglycaemia is associated with eumetabolism and that hyperglycaemia is an indicator of dysmetabolism. The authors conclude that the blood glucose value can only be accepted as a general metabolic parameter with marked limitations. The main points of this statement are that euglycemia is not always associated with eumetabolism and that acute hyperglycemia is not always associated with dysmetabolism. Different biochemical energy-producing mechanisms associated with identical blood glucose levels can support identical cell metabolic performance. At the same blood glucose level, both positive and negative metabolic balance of cell metabolism can occur. The acute stress state can be characterized by normal or elevated blood glucose values. This means that the increased metabolic activity is not reflected by the simultaneous frequently normal blood glucose measurements, i.e., there is no mandatory association between the actual blood glucose value and the metabolic state. Another finding is that chronic hyperglycemia acts as both a marker and a cause of dysmetabolism; thus, achieving near normoglycemia remains the primary therapeutic goal in diabetes treatment. Insulin administration can have a positive impact on dysmetabolic states of various origins. The central role of chronic stress in the evolution and interrelationships of various dysmetabolic states is emphasised. The transporter nature of blood glucose values substantiates discrepancies between blood glucose values and cellular metabolism; this value reflects the result of bidirectional glucose movement into and out of tissues.